Exploring health related quality of life for women with breast cancer in Ireland and Québec, Canada throughout the COVID-19 pandemic - Charlotte Myers; Kathleen Bennett; Caitriona Cahir; Josée Savard; Sophie Lauzier (Scientific Reports)
Abstract The long-term consequences from the COVID-19 pandemic on breast cancer (BC) is highly unknown, however persisting unmet needs and psychosocial difficulties are likely. The objectives of this study were to evaluate the change in health-related quality of life (HR-QoL) from the pandemic to post-pandemic for women living with a diagnosis of BC and to assess the association between COVID-19 stressor impact and HR-QoL in Ireland and Québec, Canada. Women with a diagnosis of BC were initially enrolled in the cohort study. HR-QoL was assessed during the pandemic (2020–2021) and post-pandemic periods (2022). COVID-19 stressor impact was computed post-pandemic, and change in HR-QoL during and post-pandemic was compared between Ireland and Québec using independent t-tests. Multivariable analysis of covariance (ANCOVA) was used to evaluate the association between COVID-19 stressor impact and changes in HR-QoL, and compare it between Ireland and Québec. 405 participants were included from both settings (Ireland n = 267; Québec n = 138). The average HR-QoL improved from the COVID-19 pandemic to post-pandemic, and there were no differences between Ireland and Québec. Women with high COVID-19 stressor impact (18.9% of participants) had a significantly smaller improvement in their overall HR-QoL compared to those with low COVID-19 stressor impact, and this was evident in Ireland (p < 0.004) and Québec (p < 0.0001) but there were no significant differences between Ireland and Québec (interaction p-value > 0.05). Overall, HR-QoL for women with BC improved from pandemic to post-pandemic period. However, similarly in both settings, women who experienced higher levels of COVID-19-related stress had a slower recovery in HR-QoL. These results can guide decisions about health services and policies to adequately address the on-going effect of the pandemic and also prepare for future health crises.